How to prepare students for productive and satisfying careers in the knowledge‐based economy: Creating a more efficient educational environment - Stukalina, Yulia (Technological and Economic Development of Economy, 2008)
Globalization poses new challenges to higher education institutions. The main concern for educators is to provide their graduates with an extensive assortment of skills required for the new knowledge‐based economy. To successfully address the emerging challenges education managers have to create an efficient educational environment for providing a sustaining learning process. The integrated educational environment, where students have an opportunity to develop their creative potential, is an efficient means of preparing students for productive and satisfying careers in the knowledge‐based economy. Realizing their strategy educational managers employ a variety of management practices. Integrated management practices accompany pedagogical instruments to be applied in the highly integrated educational environment. The symbiosis of pedagogical and management tools leads to the educational environment enhancement. This paper focuses on some essential educational management issues; it stresses the importance of creating the highly integrated and learner‐centred educational environment to provide multidisciplinary education.Kaip parengti studentus sėkmingai ir teikiančiai pasitenkinimą profesinei veiklai žinių ekonomikoje: efektyvesnės ugdymo aplinkos kūrimasSantrauka. Globalizacija kelia naujų iššūkių aukštojo mokslo institucijoms. Dabar pagrindinis pedagogų rūpestis – suteikti būsimiems specialistams kuo daugiau žinių naujosios žinių ekonomikos sąlygomis. Norint sėkmingai priimti kylančius iššūkius, subalansuotam mokymo procesui ugdymo planuotojai turi sukurti efektyvią ugdymo aplinką. Integruota ugdymo programa, suteikiant studentams galimybių tobulinti savo kūrybingumo potencialą, yra veiksminga priemonė, rengiant studentus sėkmingai ir pasitenkinimą teikiančiai profesinei veiklai žinių ekonomikoje. Realizuodami savo strategiją ugdymo planuotojai naudoja daug vadybos technologijų. Vadybos technologijos kartu su pedagoginėmis priemonėmis gali būti pritaikytos integruotoje ugdymo aplinkoje. Pedagoginių ir vadybos priemonių simbiozė gerina ugdymo aplinką. Straipsnyje aptariamos kai kurios svarbiausios ugdymo organizavimo problemos, pabrėžiama integruotos ugdymo aplinkos sukūrimo svarba teikiant daugiadisciplininio ugdymo paslaugas.Reikšminiai žodžiai: žinių ekonomika, vadyba, daugiadisciplininis ugdymas, ugdymo aplinka.First published online: 21 oct 2010